Characteristics of Instant Betutu Seasoning Using the Foam-Mat Drying Method - Sudiarta, I Wayan; Dewi, Ni Komang Putri Candra; Rudianta, I Nyoman; Setianingsih, Luh Putu Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Betutu is a typical Balinese food that is known to have a delicious taste because it uses various kinds of spices or base genes. Drying instant betutu seasoning using the foam-mat drying method requires foaming agents and fillers. One of the foaming and filler ingredients is egg white and maltodextrin. This research aims to determine the concentration of egg white and maltodextrin on the best chemical, microbiological, and organoleptic characteristics of instant betutu seasoning. The best research results were obtained in the treatment with a concentration of 15% egg white and 5% maltodextrin with a water content of 5.24%, ash content of 6.22%, protein content of 0.23%, acidity degree (pH) of 5.45, and total microbes of 9, 7 x 102 CFU/g. Subjective observations (color, aroma, taste, texture, and overall acceptability): 5.15–5.55, with the criteria somewhat like it.